PENGEMBANGAN PERANGKAT PEMBELAJARAN MATEMATIKA MENGGUNAKAN MODEL DISCOVERY LEARNING PADA MATERI SEGIEMPAT DAN SEGITIGA KELAS VII SMP/MTs - Nurhafizah Hayati; Armis Armis; Atma Murni (ALGORITMA: Journal of Mathematics Education, 2020)
The background of this research is the limited of mathematics learning devices that corresponds to 2013 curriculum. The purpose of this research is to produce learning devices in the form that are Syllabus, Learning Implementation Plan, and Student Activity Sheet by using discovery learning models in the material of Quadrilateral and Triangle class of VII SMP/MTs. The development model in this research used 4D model with four steps, namely define, design, develop and disseminate. The research’s instrument used were validity instruments and practicality instruments. The learning device developed were validated by three validators and revised according to the suggestions of the validator. The average results of the analysis syllabus validation was 3.75 with a very valid category and the average results for the analysis Learning Implementation Plan validation and Student Activity Sheet validation results were 3.76 with a very valid category. The results of this validation analysis show that the Syllabus, Learning Implementation Plan, and Student Activity Sheet are considered valid. Valid learning device was then tested on a small group. The results of data analysis on the practicality of using Student Activity Sheet in small group trials is 3.50 which very practical category. Based on the results of the data analysis, it can be concluded that the product of development in the form of mathematics learning devices uses discovery learning models on the material of Quadrilateral and Triangle grade VII of SMP/MTs have been assessed as valid and suitable for use.